Impact of charge-compensated Fe and Nb co-substitution on BaTiO3: Bandgap and grain size reduction and enhanced bulk photovoltaic power of Al/BFNT/Ag solar cell - Venkidu, L.; Raja, N.; Sundarakannan, B. (Solar energy, 2023)
•Al/BaTi1-2xFexNbxO3/Ag is an excellent bulk ferroelectric photovoltaic device configuration.•Increment of aliovalent Fe3+and Nb5+ionic substitutions reduces the bandgap of 0.075BFNT ceramics to ∼2.55 eV and broadens the visible spectrum absorption.•The photocurrent density of Al/0.075BFNT/Ag photovoltaic cell is about ∼ 2.2 times higher than that of pure BT.•A high photovoltaic power of ∼ 12 μW/cm2 was achieved. The generation of above bandgap photovoltage using bulk ferroelectric materials has become a subject of great interest, however, their photocurrent density is limited by a broad bandgap and poor conductivity. To overcome this limitation, we replaced aliovalent metal ions (Fe3+and Nb5+)at the B-site of robust ferroelectric BaTiO3and fabricated an Al/BaTi1-2xFexNbxO3/Ag photovoltaic device. Both the experimental and the theoretical studies showed that bandgap was lowered to ∼2.55 eV and hence absorption of wide energy range of the solar spectrum was attained. An apt top electrode, reduced bandgap and domain size resulted in greater photocurrent density of 1.46 μA/cm2 and photovoltage of 8.31 V for Al/0.075BFNT/Ag solar cell in unpoled condition. This research suggest that reduced band gap, mixed structural phases and nano-sized domains suffices greatest PV power output while the large polarization and poling are not necessary prerequisites.